E-Procurement in Preventing Fraud in The Procurement of Government Goods and Services at Semarang State University - Nining Wahyuningsih; Nury Ariani Wulansari; Ariyati; Nugroho Wahyu Pratama; Mila Kurnia Pinandita (Journal of Public Administration and Government, 2023)
Fraud is prone to occur in the procurement process of goods and services in each work unit. For this reason, the government has made it a policy that one of the ways to procure goods and services is through e-procurement. This study aims to determine the role of e-procurement in fraud prevention in the procurement of government goods and services at Semarang State University. The group of respondents are experts, members of the Working Group (MOTWG) for the Selection of Goods and Services Procurement and Quality Control at the Semarang State University Goods and Services Procurement Work Unit (GSPWU), and commitment-making officials and purchasing officers of work units. This study uses a qualitative descriptive method with a percentage, whereafter the necessary data is collected, it is classified according to a predetermined formulation, qualitative data, described in words or sentences according to predetermined categories, in a conclusion. The results showed that the application of e-procurement to fraud prevention in the procurement of government goods and services at Semarang State University has many roles, namely that transactions become economical, effective, and efficient. Besides that, e-procurement practices also play a role in preventing fraud because this does not occur directly between providers, working groups, procurement officials, and users of goods and services; all of this is done virtually.